DEWA RUCI: SEBUAH ALTERNATIF SISTEM PENDIDIKAN - Isnaniah, Siti (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2010)
The Dewa Ruci story tells us about Bratasena’s travel in finding the true life. On the way, he should obey to Durna, who is a controversial teacher and as the enemy of the Pandawa family. Along his journey, Bratasena encounters many obstacles and it makes him find out his mature, and deeper understanding of himself. Finally, Bratasena succeeds in discovering the life perfections. It is due to his loyalty to teacher, institution, and his profession. This story could be used as a reference in the education system. As an education instrument, wayang purwa offers values on teaching that could be applied by teachers. Nowadays, the puppet shows can be presented in various innovations. One of the innovation forms of Dewa Ruci Purwa Puppet played by Ki Manteb Soedharsono is packaged in the form of video compact disc including the Indonesian and English text. Dewa Ruci Purwa Puppet gives benefit to students, teachers, parents, societies, also government. Students can learn the story of Bratasena in finding the true life, the parents can learn from Dewi Kunthi the way she educates her children, and the government can improve education system by applying the values implied in the story. The education system can imitate Bratasena’s independence in finding science to get the best achievement by maintaining the motivations and the instruction of the teacher.